Treatment failure after negative pressure wound therapy in post-sternotomy mediastinitis - Schimmer, Christoph; Heinowski, Christina; Hamouda, Khaled; Meybohm, Patrick; Madrahimov, Nodir; Färber, Gloria; Radakovic, Dejan (The Thoracic and Cardiovascular Surgeon)
Background: This study investigated factors leading to treatment failure after negative pressure wound therapy (NPWT) in post-sternotomy mediastinitis (PSM) patients. Methods: A single-center retrospective case-control study in 198 cardiac surgery patients with PSM and consecutive NPWT were retrospectively divided into two groups. Group I consisted of patients whose NPWT was successful (n=117/198; 59.1%), while in Group II treatment failure occurred (n=81/198; 40.9%). Primary end-point was treatment failure, defined as re-occurrence of wound infection requiring surgical treatment within 30 days after secondary wound closure. Results: BMI > 30 kg/m2 (p=0.04; OR 1.07), Diabetes mellitus (p=0.03; OR 1.94) and the number of sponge changes (p=0.01; OR 1.57) showed an association with the occurrence of NPWT failure. During the study period 10/198 (19.8%) patients died after secondary wound healing. In group I died 1/117 (0.9%) patient versus group II with 9/81 (12.7%) patients. 70% patients died from septic multiple organ failure. Conclusion: This study confirms that variables associated with treatment failure after negative pressure wound therapy in post-sternotomy mediastinitis are BMI > 30 kg/m2, Diabetes mellitus, and the "number of sponge changes", repectively. However, this does not mean that sponge changes increase the risk; rather, sponge changes are associated with more resistant germs, incomplete wound healing and more aggressive infection. This implies that management should be in the hands of cardiac surgeons with extensive experience in septic surgery and at centers with expertise in order to minimize the duration of NPWT and thus the number of sponge changes.